Quality of Life of Greek Patients with Type 2 Diabetes and the Role of Rehabilitation (International Journal of Nursing Education, 2021)
Introduction: Diabetes mellitus is a chronic disorder that is increasing rapidly worldwide. Appropriatemanagement of this chronic disease can improve patient’s quality of life, increase life expectancy and relievesociety of the huge financial burden.Purpose: The aim of this study was to measure the quality of life of patients with type 2 diabetes and toinvestigate the role of rehabilitation.Methodology: Data were collected with the use of a questionnaire that consisted of three (3) sections:The Short Form 36 Health Survey Questionnaire, (17) questions adapted from the Diabetes SatisfactionQuestionnaire (DTSQs) and the Problem Areas In Diabetes (PAID) scale and questions regarding medicaldata and demographic information. The sample included a total of n = 122 individuals suffering from type2 diabetes. The research was carried out in outpatient clinics of two general hospitals and private practiceswithin the region of Western Greece. The results of the study were analyzed using the statistical programSPSS v.25.0.Results: Age and the existence of another health problem besides diabetes have a negative impact on thequality of life of these patients on their physical and emotional health. As patients age, their quality of lifedecreases affecting all eight scales of the SF-36 Questionnaire. In contrast, patients who had several hoursof professional work managed to have a positive outcome on all eight scales. Regarding these patient’srehabilitation, the results showed that the more satisfied the patients were regarding their treatment plan,doctor and nursing staff, their family’s support, and their diabetic diet, the grater their functionality on allscales.Conclusions: The results showed that it is important for patients with type 2 diabetes to have an activeprofessional life and follow an appropriate rehabilitation program, in order to improve their quality of life.
Keywords: Type 2 Diabetes, Quality of life, Rehabilitation.